HUBUNGAN KECEPATAN DAN DAYA LEDAK OTOT TUNGKAI TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS XI MADRASAH ALIYAH MUHAMMADIYAH BERTI PEKANBARU - Armizar '; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem of the research was lack of long jump ability for the XI grade male students in Senior High School Muhammadiyah Berti Pekanbaru. It assumed that it was lack of speed and the explosive power of leg muscle in doing long jump squat style. The aim of the research was to see the correlation of speed and the explosive power of leg muscle through long jump squat style. The research was a correlation research aiming to know how strong the relationship between independent variable and dependent variable. Then, the researcher did data normality test by using liliefors test with the significant level α = 0.05. It got variable normality X1 , L0 max ( 0.0449 ) < Ltable ( 0.190 ), and variable normality X2, L0max ( 0.692 ) < Ltable ( 0.190 ) with normality test Y, L0max ( 0.0728 ) Ltable (0.190 ), in other word the data was nomal distributive data. Then, the r score was datermined by using analysis correlation of product moment. If rcount > rtable, it meant that there was a significant correlation. According to the result of the correlation of the explosive power of leg muscle through long jump squat style, it resulted rcount 0.943 and rtable 0.456. The result of the correlation of correlation of the explosive power of leg muscle through long jump squat style, it resulted rcount 0.834 and rtable 0.456. Determining R variables X1 and X2 through Y used the formula of double correlation with rcount 0.872 and rtable 0.456, so Ho was refused and Ha was accepted. In conclusion, there was a significant correlation of speed and the explosive power of leg muscle in doing long jump squat style for XI grade students of senior high school Muhammadiyah Berti Pekanbaru.Keywords : speed, the explosive power of leg muscle, long jump